2016
DOI: 10.1016/j.gendis.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells and HER2 positive breast cancer: The story so far

Abstract: Human Epidermal Growth Factor Receptor type 2 (HER2) gene amplification and/or protein overexpression is observed in patients suffering from HER2+ breast cancer. This subtype of breast cancer has improved prognosis due to availability of anti-HER2 therapy. However, drug resistance and tumor recurrence still remains a major concern. Cancer Stem Cells (CSCs) are believed to constitute the subset of cell population that is resistant to drug treatment and possesses characteristics of stem cells. CSCs enable the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…The tyrosine-phosphorylation of ErbB2 leads to the activation of the PI3K-AKT, Ras-Raf-MEK-ERK, and JAK-STAT signalling pathways 15,2730,32 . We therefore examined the effects of nectin-4 on the activation of these signalling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The tyrosine-phosphorylation of ErbB2 leads to the activation of the PI3K-AKT, Ras-Raf-MEK-ERK, and JAK-STAT signalling pathways 15,2730,32 . We therefore examined the effects of nectin-4 on the activation of these signalling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro tumorigenic assay, knocking down ESE-1 significantly inhibited tumorsphere formation, revealing that ESE-1 contributes to the maintenance of tumor initiating cells (Figure 8 ). Previous reports have established that the HER2/PI3K/Akt signaling axis is critical to proliferation and sustenance of tumor initiating cells [ 34 , 50 , 51 ]. In addition, the NF-KB, IL-8-CXCR1/2, JAK-STAT axes have been implicated in promoting self-renewal and differentiation of HER2 + breast cancer stem cells [ 34 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have established that the HER2/PI3K/Akt signaling axis is critical to proliferation and sustenance of tumor initiating cells [ 34 , 50 , 51 ]. In addition, the NF-KB, IL-8-CXCR1/2, JAK-STAT axes have been implicated in promoting self-renewal and differentiation of HER2 + breast cancer stem cells [ 34 , 50 , 51 ]. As mentioned above, we found that expression of some of these key genes are altered upon ESE-1 knockdown ( Supplementary Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, breast cancer is one of the most common cancers in women that can be treated with lumpectomy, mastectomy, radiation therapy, chemotherapy, and so on [1–3]. Defining the characteristics of breast cancer is important for classifying its subtypes, understanding the disease prognosis, and determining a suitable therapy.…”
mentioning
confidence: 99%
“…Defining the characteristics of breast cancer is important for classifying its subtypes, understanding the disease prognosis, and determining a suitable therapy. Estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and Ki67 are the known prognostic and predictive markers for breast cancer [1–3]. According to immunohistochemical and gene expression studies on ER, PR, HER2, and Ki67, human breast cancers are classified into the following subtypes: luminal A‐like (ER+/PR+/HER2−/low Ki67), luminal B/HER2‐negative‐like (ER+/PR+−/HER2−/high Ki67), luminal B/ HER2‐positive‐like (ER+/PR+−/HER2+), HER2‐positive (ER−/PR−/HER2+), and triple‐negative (ER−/PR−/HER2−) [1–3].…”
mentioning
confidence: 99%